Conversion to Sirolimus Therapy in Kidney Transplant Recipients with New Onset Diabetes Mellitus after Transplantation - Massimiliano Veroux; Tiziano Tallarita; Daniela Corona; Nunziata Sinagra; Alessia Giaquinta; Domenico Zerbo; Carmela Guerrieri; Antonino D'Assoro; Sebastiano Cimino; Pierfrancesco Veroux (Clinical and Developmental Immunology)
New-onset diabetes mellitus after transplantation (NODAT) may complicate 2–50% of kidney transplantation, and it is associated with reduced graft and patient survivals. In this retrospective study, we applied a conversion protocol to sirolimus in a cohort of kidney transplant recipients with NODAT. Among 344 kidney transplant recipients, 29 patients developed a NODAT (6.6%) and continued with a reduced dose of calcineurin inhibitors (CNI) (8 patients, Group A) or were converted to sirolimus (SIR) (21 patients, Group B). NODAT resolved in 37.5% and in 80% patients in Group A and Group B, respectively. In Group A, patient and graft survivals were 100% and 75%, respectively, not significantly different from Group B (83.4% and 68%, resp., P=0.847). Graft function improved after conversion to sirolimus therapy: serum creatinine was 1.8 ± 0.7 mg/dL at the time of conversion and 1.6 ± 0.4 mg/dL five years after conversion to sirolimus therapy (P<0.05), while in the group of patients remaining with a reduced dose of CNI, serum creatinine was 1.7 ± 0.6 mg/dL at the time of conversion and 1.65 ± 0.6 mg/dL at five-year followup (P=0.732). This study demonstrated that the conversion from CNI to SIR in patients could improve significantly the metabolic parameters of patients with NODAT, without increasing the risk of acute graft rejection.